2005
DOI: 10.4018/978-1-59140-819-2.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of E-Commerce Applications in SMEs

Abstract: Personalization of e-commerce applications is an issue that is gaining increasing importance with the advancing maturity of such systems. There is already e-commerce software on the market offering integrated e-shop and personalization functions. However, the available software is too time-consuming and expensive for SMEs. With this in mind we saw a need to investigate the potential for personalization from the particular angle of SMEs. In addition to some theoretical fundamentals of personalization, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…ERP systems have been the subject of a huge number of studies (ample and categorised bibliographies can be found in Esteves and Pastor, 2001; Møller et al , 2004; Esteves and Bohorquez, 2007) that, from various theoretical perspectives, dealt with aspects such as characteristics, adoption and implementation processes (Nandhakumar et al , 2004; Butler and Pyke, 2003), favourable context elements (Sammon and Adam, 2004), project design and/or execution (Laframboise, 2002), organisational impacts (Holland et al , 1999; Westrup and Knight, 2000), forecasting of the probability of success (Magnusson et al , 2004), future outlook (Markus et al , 2000a), extension towards e‐commerce (Schubert and Leimstoll, 2004; Kemppainen, 2004; Schubert, 2003), and ERP's strategic role as the solution sought by managers for all their problems (Sammon and Adam, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…ERP systems have been the subject of a huge number of studies (ample and categorised bibliographies can be found in Esteves and Pastor, 2001; Møller et al , 2004; Esteves and Bohorquez, 2007) that, from various theoretical perspectives, dealt with aspects such as characteristics, adoption and implementation processes (Nandhakumar et al , 2004; Butler and Pyke, 2003), favourable context elements (Sammon and Adam, 2004), project design and/or execution (Laframboise, 2002), organisational impacts (Holland et al , 1999; Westrup and Knight, 2000), forecasting of the probability of success (Magnusson et al , 2004), future outlook (Markus et al , 2000a), extension towards e‐commerce (Schubert and Leimstoll, 2004; Kemppainen, 2004; Schubert, 2003), and ERP's strategic role as the solution sought by managers for all their problems (Sammon and Adam, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also obstacles with a possibly different relevance or thresholds in comparison with larger companies, such as initial costs (Schubert and Leimstoll, 2004; Schubert, 2003), redesign of typical internal processes (Westrup and Knight, 2000), the length of the software introduction cycle, and the “cultural” resistance of people involved in the project (Kemppainen, 2004), because the technical integration of an ERP system also requires a social integration (Elbanna, 2003). To overcome these problems once and for all, some authors have even suggested the construction of a proprietary integrated system by each SME, through direct software development, possibly incorporating market‐acquired modules for the most standardized functions (Olsen and Sætre, 2007b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, the current ERP systems adoption rate in MSMEs is still low, and numerous cases have been reported where even after implementation, organizations are still depending on their legacy systems and even treating the cost incurred in implementation as a sunk cost. Such a scenario raises some serious questions: can certain factors be identified that can be considered critical in context to Indian MSMEs on account of their peculiarities (Tagliavini et al, 2002;Schubert, 2003)?…”
Section: Introductionmentioning
confidence: 99%